A Comparative Study of the Creatinine Clearance in 12-hour and 24-hour Timed Urine Collection in Healthy Volunteer - Raj Kumar Yadav; Binod Yadav; Anitha Devanath (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 1-5